The phenomenon of RNA interference in oncology: advances, problems and perspectives - O. E. Andreeva; M. A. Krasil’nikov (Успехи молекулярной онкологии)
Review describes the phenomenon of RNA interference – the recently discovered biological mechanism of the negative regulation of gene expression. The mechanism is based on the block of the translation and/or degradation of messenger RNA under short non-coding RNA, among them: microRNA and small interfering RNA. The paper reviews the molecular processes of the formation of small RNA, the mechanism of their action and the feasibility of small RNA implementation in the anti-tumor therapy. Specially, we analyze the approaches to in vivo delivery of small RNA, in particular – the liposome and exosome constructs, and perspectives of the involvement of such constructs in the cancer treatment.